Practice of physical activity and alcohol consumption in adolescent schoolchildren - Guevara-Ingelmo, Raquel María; Guevara-Valtier, Milton Carlos; Urchaga-Litago, José David; Sánchez-Moro, Esther (Horizonte Sanitario, 2022)
Objective: To know the habits that Secondary Education students present in physical activity and alcohol consumption and the possible correlations that exist between these two habits according to the sex of the respondents.Materials and method: A descriptive cross-sectional study is presented in which 656 Secondary School students from the city of Salamanca in Spain participated. The sampling was multistage random, stratified by conglomerates, and the questionnaire from the HBSC study sponsored by the World Health Organization was used as an instrument for collecting information.Results: The results show differences according to the sex of the respondents in both habits, with boys practicing more physical activity than girls and also consuming alcohol more frequently. On the other hand, no relationship was found between the practice of physical activity and the consumption of alcohol, both showing being independent.Conclusions: Sex seems to be a relevant variable in the practice of physical activity and alcohol consumption in adolescence. Although it was hypothesized that the practice of physical activity is a protective factor against alcohol consumption, in this research there does not seem to be a correlation between both habits so that a young person can, in turn, practice physical activity on a regular basis and be habitual consumer of alcohol. Finally, given these results, global measures are proposed that favor the acquisition and maintenance of healthy behaviors at this stage of development.Keywords: Adolescence, Physical activity, Alcohol, Secondary education.